ANALISIS PERILAKU CYBERBULLYING DI MEDIA SOSIAL PADA MAHASISWA BIMBINGAN KONSELING UNIVERSITAS TEKNOLOGI YOGYAKARTA - Vera Agustiningrum; Ari Prasetyoaji (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The increase in technology users and internet networks can increase the possibility of someone experiencing cyberbullying, both as a perpetrator and victim. This study aims to look at cyberbullying behavior in Guidance and Counseling students at Yogyakarta University of Technology. This research uses a qualitative method. The results showed that the forms of cyberbullying behavior carried out by UTY counseling guidance students are flaming (anger), harassment (harassment), denigration (defamation) and outing (information leakage) and also social media used to carry out cyberbullying are Whatsapp and Instagram. Factors that influence cyberbullying include hurt feelings, peer association and the use of social media. The impact felt by victims is that they feel less confident, embarrassed and more careful in choosing the content to be uploaded on social media, and more vigilant in acting so that they are not always considered wrong by others.